2023
DOI: 10.1108/ejim-03-2022-0144
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable leadership and heterogeneous knowledge sharing: the model for frugal innovation

Abstract: PurposeConsidering the vital role of resource-constraint innovation in developing countries, the aim of the study is to examine the mechanism of internal and external heterogeneous knowledge sharing (HKS) in the relationship between sustainable leadership (SL) and frugal innovation (FI). The social exchange theory was used to develop a research framework.Design/methodology/approachThis study employed Partial Least Squares Structural Equation Modeling (PLS-SEM) analysis to examine the relationship among several… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 101 publications
1
29
1
Order By: Relevance
“…Moreover, the study offers new insight into conditional variables that influence the relationship between GHRM and employee behaviors. Previous research focused on organization-level variables serving as moderators, such as CEO leadership (Ren et al, 2021), managerial environmental concern (Song et al, 2020) and green knowledge sharing (Iqbal and Piwowar-Sulej, 2023b). Although managers' behavior has been found to be an important factor that stimulates EGBs (Zhang et al, 2021), to the best of the authors' knowledge, no study to date has been conducted using EMS as a conditional variable between GHRM and EGBs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the study offers new insight into conditional variables that influence the relationship between GHRM and employee behaviors. Previous research focused on organization-level variables serving as moderators, such as CEO leadership (Ren et al, 2021), managerial environmental concern (Song et al, 2020) and green knowledge sharing (Iqbal and Piwowar-Sulej, 2023b). Although managers' behavior has been found to be an important factor that stimulates EGBs (Zhang et al, 2021), to the best of the authors' knowledge, no study to date has been conducted using EMS as a conditional variable between GHRM and EGBs.…”
Section: Discussionmentioning
confidence: 99%
“…, 2021), managerial environmental concern (Song et al. , 2020) and green knowledge sharing (Iqbal and Piwowar-Sulej, 2023b). Although managers’ behavior has been found to be an important factor that stimulates EGBs (Zhang et al.…”
Section: Discussionmentioning
confidence: 99%
“…Sustainable leaders – who show their true concern about the environment and treat employees as important stakeholders – act as role models for their followers. Moreover, they strengthen the learning process by sharing knowledge and introducing employee participation and empowerment (Iqbal and Piwowar-Sulej, 2023). They value employees' green behavior and thus also directly contribute to a green organizational climate.…”
Section: Discussionmentioning
confidence: 99%
“…External factors include macroeconomic factors, economic policies, financial markets, industry technology, and upstream and downstream supply chains (Appiah et al, 2019; Cardoza et al, 2015), whereas internal characteristics mainly include productivity, managerial characteristics, financial capabilities, and innovation (Bianchi & Stoian, 2022; Di Gregorio et al, 2009; Zimon et al, 2022). In the era of digital economy, the speed of knowledge diffusion is accelerating (Salehi & Sadeq Alanbari, 2023), and a large number of empirical studies have shown that information technology or digital technology is a key force in enhancing the international competitiveness of SMEs (Peña-Vinces et al, 2012; Wen et al, 2022).…”
Section: Background and Theoretical Analysismentioning
confidence: 99%